Development of a Chemistry E-Module Based on a Problem Based Learning Model on Reaction Rate Material - Tambunan, Kasandra Louisa; Damanik, Marini (Jurnal Pendidikan dan Pembelajaran Kimia, 2024)
Abstract: Development of a Chemistry E-Module Based on a Problem Based Learning Model on Reaction Rate Material. This research uses the 4D model Research and Development (R&D) method starting from the definition, design, development and distribution stages. The research was limited to the development stage, namely determining the level of validity and small-scale trials to see responses from teachers and students at SMA Negeri 1 Percut Sei Tuan.  The product that will be produced is a chemistry e-module based on Problem Based Learning which contains a review of reaction rate material. Data collection used validation questionnaires and teacher and student response questionnaires.The validation assessment involved five expert validators including two media expert validators and three material expert validators. The media expert assessment was 87.8% which met very valid criteria and the material expert assessment was 80.5% with very valid criteria. Therefore, the rate e-module using the problem based learning model is suitable for use in the learning process. The teacher practicality test was carried out and a result of 98% was obtained which met the very practical criteria. The results of 32 students' responses to the e-module were 82.9% with strongly agree criteria. It was concluded that the Chemistry E-Module based on the Problem Based Learning Model on Reaction Rate Material could increase students' motivation in learning. Keywords: E-Module; Reaction rate; Problem Based Learning.